Efficiency and Equity in a Society-Economy Integrated Model - Marc Fleurbaey; Ravi Kanbur; Dennis J. Snower (Center for Economic Studies and ifo Institute (CESifo), 2021)
A model that only focuses on economics relations, and in which efficiency and equity are defined in terms of resource allocation may miss an important part of the picture. We propose an integrated model that embeds economic activities in a larger game of social interactions, and define comprehensive notions of efficiency and equity. Social interactions provide additional sources of inefficiencies and inequalities, including through the mere lack of coordination between the regulation mechanisms of the economics sphere and the social sphere. Remedies may require more than market solutions and redistribution of resources. In particular, social norms are likely to play an important role.
Keywords: 330